Regenerating contemporary city between experimentation and education - Laura Ricci; Irene Poli (Agathón)
The Paper aims to contribute at the comparison debate between Schools of Architecture, Engineering and Design, through the illustration of an educational experience developed by the Department of Planning, Design and Technology of Architecture, Sapienza University of Rome. The Workshop ‘Redeveloping, regenerating, and transforming the contemporary city. Towards a strategy of integration and of restoring urban and metropolitan balance’ organized with the University of Valladolid and with the Universidad of Castilla-La Mancha, aims to address, in cultural, disciplinary and experimental terms, the theme of role of regeneration strategies in the government processes of the contemporary city.